Soro de queijo associado ao colostro sobre o desempenho de bezerros - Lima, Renata Nayhara de (Universidade Federal Rural do Semi-Árido, 2012)
This study aimed to evaluate the performance and yield components of carcass and non-carcass of calves fed whey associated with colostrum feeding of crossbred calves in 60 days, besides conducting the economic analysis of substitution. We used 24 male calves, Holstein x SPRD, distributed in a completely randomized design with three treatments and eight replicates: Whole milk (control), 50% whole milk + 50% of cheese whey in natura; 30% Colostrum + 70% Serum fresh cheese. The development of the calves was evaluated by weekly weighings and measurements of body withers height, hip height, heart girth and body length. To estimate consumption measurements were made daily consumption of hay and concentrate offered by the method / spare. The animals were slaughtered at 60 days, where measures were taken for pH and temperature at slaughter and after 24 hours. Were also parameters for carcass and non-carcass components. The evaluation consisted of calculating economic performance indicators of costs and revenues, and measures of economic outcomes. All variables were tested with mean comparison Tukey, 5% probability. The weekly intake of total dry matter intake, weight gain and body measurements evaluated did not differ between treatments (P> 0.05). There were no significant differences (P> 0.05) between treatments for the variables of carcass traits and non-carcass components. The treatment containing 70% whey + 30% of colostrum had additional income of R$ 126,86 and this was mainly attributable to spending on a liquid diet. The results show that the substitution of milk for cheese whey shown a very feasible alternative, associate it with colostrum enable further expand its potential use
Whey cheese associated colostrum on performance of calves
Keywords: Body measurements; Carcass; Consumption; meat cuts; Substitute; Carcaça; Consumo; Cortes cárneos; Medidas corporais; Sucedâneo; CIENCIAS AGRARIAS::MEDICINA VETERINARIA